2022
DOI: 10.1186/s13104-022-06018-y
|View full text |Cite
|
Sign up to set email alerts
|

Excess all-cause mortality and COVID-19 reported fatality in Iran (April 2013–September 2021): age and sex disaggregated time series analysis

Abstract: Objective The actual impact of the pandemic on COVID-19 specific mortality is still unclear due to the variability in access to diagnostic tools. This study aimed to estimate the excess all-cause mortality in Iran until September 2021 based on the national death statistics. Results The autoregressive integrated moving average was used to predict seasonal all-cause death in Iran (R-squared = 0.45). We observed a 38.8% (95% confidence interval (CI) 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…In addition, androgens, especially testosterone, are considered a possible risk factor [ 66 ]. Populations older than 60 years had higher excess mortality, and several country studies also indicate the same results [ 42 , 45 , 67 , 68 ]. We believe that the senior population has lower physical function and immunity compared to younger people, and they are more susceptible to the neo-crown virus during the pandemic [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In addition, androgens, especially testosterone, are considered a possible risk factor [ 66 ]. Populations older than 60 years had higher excess mortality, and several country studies also indicate the same results [ 42 , 45 , 67 , 68 ]. We believe that the senior population has lower physical function and immunity compared to younger people, and they are more susceptible to the neo-crown virus during the pandemic [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 64%
“…After exclusion, 439 studies were eligible for full-text review. The final meta-analysis comprised 20 eligible studies ( Figure 1 ), References [ 15 , 21 , 24 , 25 , 26 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] of which 79 countries were included in the study ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies (30,31) suggest that the actual death toll from COVID-19 in Iran is much higher than the o cially reported gures. This is likely due to a number of factors, including limited testing capacity, lack of access to healthcare, and stigma associated with COVID-19 (32). This study found that there were an estimated 178.86 excess deaths per 100,000 population in Iran during the study period, with a higher increase among males and older adults.…”
Section: Authoritarian Nations With Low Police Intervention Levels (Alp)mentioning
confidence: 73%
“…Mean BMI was 22.9 + 3.71 kg/m 2 , and O, A, B, and AB blood groups were evident in 35.85, 31.7, 22.48, and 10% of students, respectively. Of 180 reported comorbidities, asthma ( 31 ) and thyroid gland disorders ( 26 ) were among the most frequent underlying diseases. All the patient’s demographic information and their history of COVID-19 infection are given in Table 1 .…”
Section: Resultsmentioning
confidence: 99%